2020
DOI: 10.4103/jiaps.jiaps_80_19
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal gastric perforation: Our experience and important preoperative and intraoperative caveats to prognosticate and improve survival

Abstract: Aim: Neonatal gastric perforation (NGP) is a rare, perplexing, life-threatening entity affecting neonates. We share our experience of operating upon cases of NGP s and highlight important points observed which may aid in further improving care of neonates, diagnosed with this entity. Materials and Methods: A retrospective analysis of all consecutive patients with NGP operated by the author, at various centers between January 2015 and December 2018, was carried out. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…4,16 Prematurity and low birthweight have been consistently reported to be associated with gastric perforations in neonates as was observed in our review. 6,12,15,[17][18][19] In 1943, Herbut et al reported congenital absence of musculature on the stomach in a case of spontaneous NGP, which has since been reported in a few other reports. 4 In seven neonates who died of idiopathic gastric perforation, Oshiro et al noted the absence of interstitial cells of Cajal (ICC) in three stomachs and decreased in four stomachs.…”
Section: Discussionmentioning
confidence: 99%
“…4,16 Prematurity and low birthweight have been consistently reported to be associated with gastric perforations in neonates as was observed in our review. 6,12,15,[17][18][19] In 1943, Herbut et al reported congenital absence of musculature on the stomach in a case of spontaneous NGP, which has since been reported in a few other reports. 4 In seven neonates who died of idiopathic gastric perforation, Oshiro et al noted the absence of interstitial cells of Cajal (ICC) in three stomachs and decreased in four stomachs.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, studies have shown increased mortality with increasing size of perforation with perforation >1.5 cm being associated with poor outcomes. 11,22 The baby in our case had 3 perforations, the largest being 1 × 0.5 cm, and had an excellent outcome after the procedure.…”
Section: Discussionmentioning
confidence: 58%
“…8 Defects in the muscular layer of the gastric wall, especially among preterms, during ventilatory management for tracheo-esophageal fistula repair, hypoxic/ischemic necrosis and perforation, sepsis, duodenal/jejunal obstruction, use of the ibuprofen-paracetamol, necrotizing enterocolitis, excessive feeding are the reported causes of gastric perforation. 7,[9][10][11][12][13][14] In premature infants, owing to the fragility of the gastric wall, relatively minor traumatic events (insertion of nasogastric tube and/or gastric distension during bag-mask ventilation) may bring about a local gastric wall disruption and perforation. 7 In the case of a punctate perforation, a traumatic factor should be considered, such as the use of gastric tubes.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is no evidence to suggest that the site of perforation predicts mortality; however, the size is an important prognostic factor. 5 Prompt surgical intervention is important and the most performed surgical procedure is suture of the perforation (gastrorrhaphy) alone or combined with gastrostomy. 2 These techniques are preferred over a sleeve gastrectomy because of the associated feeding difficulties.…”
Section: Discussionmentioning
confidence: 99%